Valoración con opciones reales del proyecto de expansión de la empresa Lácteos Rincón del Toro en el campo de la producción de lácteos de origen caprino - García-Pacheco, Sebastián; Guzmán-Siles, Rubén (Instituto Tecnológico de Costa Rica, 2014)
ABSTRACT The present work is a contribution in the field of project appraisal for decision -making. The target company is called Lacteos Rincón del Toro which was selected after a first approach with their owners. The company was willing to provide confidential financial information in order to receive a business plan that would allow them to have a solid financial base for decision-making and selection of projects that will allow them to grow in the field dairy industry in Costa Rica. To start this study, we applied a traditional valuation model which is net present value (NPV), followed by a Real Options Analysis (RO) with the Black- Scholes method of expansion project in the company Lacteos Rincón del Toro. The project assessed is the construction of infrastructure for raising and milking goats, with that, the owners are expecting to stop buying milk from other producers achieving a decrease in the cost of materials and an increase in the use of resources such as space that are available. The idea was born in the final class of our Master degree program called Strategic Finances and what we intend to show is the great importance of variables such as uncertainty, flexibility for decision making and volatility in the financial area of the assessment of the results of projects and our investments. The expansion project consists of constructing a building to house both young goats in development as those who are already milking, its size is 8 meters by 20 meters and its 160mts2 construction will be made of wood. The investment will have a final cost estimate of 5,000,000 colones. The result of the evaluation shows that it is profitable generating an expected NPV of 712.144,00 colones. Later the assessment performed by conducting a Black- Scholes model gave a value of 4.625.995,44 colones for choice of this project and is thus demonstrating not only that the method of real options valuation, which considers factors not measured by traditional methods, gives us a more accurate view of the reality in business especially in those in which decision making can be given a time horizon, but also the project expansion in the milk of goat and its derivatives is feasible and generates value to the company, but that this value does not represents a high percentage of savings out of the total equivalent of the company. The project should be done but also the company needs to make more in-depth evaluations of the projects, in which their funds are used their real impact. Parallel to the mentioned we sensitizations were performed with other variables related to costs which gave us north into other aspects that the company should consider for future projects in order to achieve higher growth, lower costs and better yields
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2014.
Keywords: Evaluación de proyectos; Productos lácteos; Reducción de costos; Leche de cabra